Seorang Anak Usia 7 Bulan dengan Bronkopneumonia - Regina Keumala Sabty; Elli Kusmayati (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2025)
Bronchopneumonia (BP) is the most common clinical manifestation of pneumonia in the pediatric population. BP is an acute inflammation of the lung parenchyma involving the bronchi or bronchioles to the alveoli, with a patchy consolidation distribution centered around the bronchi that are multifocally inflamed, usually bilateral. Bronchopneumonia in children has typical clinical symptoms, generally preceded by an upper respiratory tract infection, such as nasal congestion, fussiness, and decreased appetite. These symptoms are then followed by sudden fever reaching 39–40˚C or more, restlessness, and respiratory distress characterized by dyspnea, rapid and shallow breathing, use of accessory muscles, nasal flaring, and mouth breathing. Within a few days, respiratory symptoms may worsen. The basis of bronchopneumonia management in hospitalized patients is causal treatment with appropriate antibiotics based on the suspected etiology, as well as supportive measures such as oxygenation and hydration. This case report will discuss a pediatric patient with bronchopneumonia, the diagnostic approach, and the therapeutic management provided to achieve optimal clinical improvement.